(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
Pathogens can be detected from asymptomatic fish using molecular diagnostic methods so disease outbreak could be prevented. Several years ago, molecular techniques have been employed to diagnose fish diseases. These methods include the polymerase chain reaction (PCR), restriction enzyme digestion, probe hybridization, in situ hybridization, and microarray. This paper reviews a step by step guide for carrying out molecular diagnosis of fish disease. However, the application of molecular methods as a routine tool in a diagnostic laboratory in areas where relevant literatures is scarce is important for the adoption of these methods.